A "CLEAN CASE" OF SYSTEMIC INJURY: MESENTERIC LYMPH AFTER HEMORRHAGIC SHOCK ELICITS A STERILE INFLAMMATORY RESPONSE. Issue 4 (October 2015) - Yi, Jeniann; Slaughter, Anne; Kotter, Cassandra V.; Moore, Ernest E.; Hauser, Carl J.; Itagaki, Kiyoshi; Wohlauer, Max; Frank, Daniel N.; Silliman, Christopher; Banerjee, Anirban; Peltz, Erik
Abstract : ABSTRACT: Postinjury multiple organ failure results from an inappropriate overwhelming immune response to injury. During trauma and hemorrhagic shock (T/HS), mesenteric ischemia causes gut mucosal breakdown with disruption of the intestinal barrier. It has been proposed that this releases the gut microbiota systemically via postshock mesenteric lymph (PSML), engendering infectious complications. Despite extensive investigation, no clear evidence has been presented for gut bacterial translocation after resuscitation from T/HS. However, such previous studies were limited by available technologies. More sensitive methods, such as quantitative polymerase chain reaction, have since emerged for detection of bacterial presence and danger-associated molecular patterns (DAMPs). Quantitative polymerase chain reaction was applied to PSML derived from a rat model of T/HS. No bacterial presence was detected in a series of 12 samples, whereas multiple lymph samples showed the presence of DAMPs after T/HS. Thus, we confirmed that bacterial translocation does not exist in PSML after resuscitation from T/HS-associated mesenteric ischemia. However, T/HS does increase the presence of mitochondrial DAMPs in PSML. These results support our current position that PSML elaborates remote organ injury by multiple inflammatory mechanisms, including lipid-mediated proinflammatory stimuli, and by contribution from gut-derived DAMPs. Abstract : Supplemental Digital Content is available in the text